A New Method for the Microdetermination of Para Aminophenol in Generic Brands of Paracetamol Tablets (2019)
In Nigeria, paracetamol is readily available in several retail outlets where the conditions of storage can be poor leading to elevated levels of para-aminophenol (PAP), which is known to be nephrotoxic and hepatotoxic. However, the routine analysis of PAP is mostly by chromatographic separation which requires expensive instrumentation not often available in developing countries. The objective of this research was to develop a sensitive colorimetric method for the quantification of PAP in paracetamol. The method was based on the diazo coupling reaction between diazotised PAP and chromotropic acid. Various reaction parameters critical for optimal detector response were optimized. The validation of the new method was done following the determination of parameters including repeatability, reproducibility and selectivity using current ICH guidelines. The new method was also applied to the assay of PAP in 14 paracetamol tablet samples. The calibration was linear between 0.0297 and 0.2229 mg/mL at 470nm with limits of detection and quantification of 0.0061 and 0.0185 mg/mL, respectively. The recovery was in the range of 95.96 and 102.21 while intra- and inter-day precisions at three different concentrations did not exceed 4.03%. The new method was successfully applied to quantify PAP in paracetamol with percent content varying from 0.14 to 0.21%w/w. A simple and reliable method for the quantification of PAP has been developed and successfully employed to report, for the first time, the presence of the degradation product at levels beyond the allowable limits in paracetamol dosage forms in Nigeria.